2001
DOI: 10.1038/sj.jhh.1001253
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and renal failure: effects on large artery stiffness

Abstract: Diabetes mellitus and end-stage renal disease are two pathologic entities associated with increased cardiovascular risk. Several studies have shown that arterial stiffness is increased in both cases and contributes to the increased risk. In order to determine the effect of diabetes and renal failure on arterial stiffness, we conducted a case-control study. One hundred and twentytwo diabetic patients were compared to 122 non-diabetic patients matched to the study group for sex, age, mean arterial pressure, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 42 publications
3
50
0
5
Order By: Relevance
“…Aoun et al (25) reported that aortic PWV correlated with GFR in patients with diabetes (type unspecified), who had a mean GFR of 81 Ϯ 24 ml/min per 1.73 m 2 . They did not examine the association of arterial stiffness with albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Aoun et al (25) reported that aortic PWV correlated with GFR in patients with diabetes (type unspecified), who had a mean GFR of 81 Ϯ 24 ml/min per 1.73 m 2 . They did not examine the association of arterial stiffness with albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…10 Little is known about the effect of both high blood pressure (BP) and DM on aortic stiffness. [11][12][13] The aim of our study was to evaluate the influence of BP and type II DM on aortic stiffness in patients with one disease or the other compared to those with both HT and type II DM.…”
Section: Introductionmentioning
confidence: 99%
“…Five donors (4.9%) developed Ն1 CV event (total, 7), whether coronary, cerebral, aortic, or peripheral. 6 …”
Section: Donors (Table 1)mentioning
confidence: 99%
“…5 After donation, 6 donors (5.9%) developed diabetes, defined by a fasting blood sugar Ͼ7 mmol/L and/or antidiabetic medication (sulfonylurea, biguanide, and/or insulin). 6 At the time of the study, 48 donors (47.5%) were hypercholesterolemic (defined by a total cholesterol/high-density lipoprotein ratio Ͼ5 and/or statin therapy), and 5 (4.9%) were taking a statin; 29 (28.7%) had metabolic syndrome, defined by the presence of 3 of the 5 criteria of the National Cholesterol Education Program's Adult Treatment Panel III report. 7 Nineteen donors (18.8%) had developed hypertension, defined by systolic blood pressure (BP) Ͼ140 mm Hg and/or diastolic BP Ͼ90 mm Hg, on Ն3 casual measurements by mercury sphygmomanometer in the supine position in the previous month or by antihypertensive therapy for previously diagnosed hypertension; 18 (17.8%) were taking antihypertensive therapy at the time of the study.…”
Section: Donors (Table 1)mentioning
confidence: 99%